Exploring public perceptions and awareness of Parkinson's disease: A scoping review. - Sophie Crooks; Gillian Carter; Christine Brown Wilson; Lisa Wynne; Patrick Stark; Michail Doumas; Matthew Rodger; Emma O'Shea; Gary Mitchell (PLoS ONE)
Background Parkinson's disease (PD) is a common neurological disease affecting around 1% of people above sixty years old. It is characterised by both motor and non-motor symptoms including tremor, slow movement, unsteady gait, constipation and urinary incontinence. As the disease progresses, individuals living with the disease are likely to lose their independence and autonomy, subsequently affecting their quality of life. People with PD should be supported to live well within their communities but there has been limited research regarding what the public know about PD. This review aims to develop an understanding of how the public view people living with PD, which has the potential to aid the development of an educational resource for the future to improve public awareness and understanding of PD. The purpose of this scoping review is to review and synthesise the literature on the public perception and attitudes towards people living with PD and identify and describe key findings. Aim This scoping review aims to explore public perceptions and awareness of Parkinson's Disease among diverse populations, encompassing beliefs, knowledge, attitudes, and the broader societal context influencing these perceptions. Methods A scoping review of the literature was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for ScR (PRISMA-ScR). Four electronic databases were searched systematically (CINAHL Plus, Medline, PsycINFO and International Bibliography of the Social Sciences). The Joanna Briggs Institute Critical Appraisal Tools (JBI) were used to assess the quality of primary studies, however, all relevant studies were considered regardless of their methodological quality. The 'Population-Concept-Context' framework was used in the screening process to identify eligible papers. Results A total of 23 studies were included in the review representing global research in quantitative (n = 12) and mixed methods approaches (n = 11). All 23 studies adopted some aspect of cross-sectional design. Three themes emerged from the studies, the first being public knowledge of symptoms, causes and treatment of PD and this highlighted a lack of understanding about the disease. Secondly, the review identified public attitudes towards PD, highlighting the social consequences of the disease, including the association between PD and depression, isolation and loss of independence. Finally, the third theme highlighted that there was a paucity of educational resources available to help increase public understanding of PD. Conclusion Findings from this scoping review have indicated that public awareness of PD is a growing area of interest. To our knowledge, this is the first scoping review on this topic and review findings have indicated that public knowledge and attitudes towards PD vary internationally. The implications of this are that people with PD are more likely to be a marginalised group within their communities. Future research should focus on understanding the perception of the public from the perspective of people with PD, the development of interventions and awareness campaigns to promote public knowledge and attitude and further high-quality research to gauge public perceptions of PD.